Bacillus subtilis RecA and its accessory factors, RecF, RecO, RecR and RecX, are required for spore resistance to DNA double-strand break - Vlašić, Ignacija (Oxford University Press, 2014)
Bacillus subtilis RecA is important for spore resistance to DNA damage, even though spores contain a single non-replicating genome. We report that inactivation of RecA or its accessory factors, RecF, RecO, RecR and RecX, drastically reduce survival of mature dormant spores to ultrahigh vacuum desiccation and ionizing radiation that induce single strand (ss) DNA nicks and double-strand breaks (DSBs). The presence of non-cleavable LexA renders spores less sensitive to DSBs, and spores impaired in DSB recognition or end-processing show sensitivities to X-rays similar to wild-type. In vitro RecA cannot compete with SsbA for nucleation onto ssDNA in the presence of ATP. RecO is sufficient, at least in vitro, to overcome SsbA inhibition and stimulate RecA polymerization on SsbA-coated ssDNA. In the presence of SsbA, RecA slightly affects DNA replication in vitro, but addition of RecO facilitates RecA-mediated inhibition of DNA synthesis. We propose that repairing of the DNA lesions generates a replication stress to germinating spores, and the RecA·ssDNA filament might act by preventing potentially dangerous forms of DNA repair occurring during replication. RecA might stabilize a stalled fork or prevent or promote dissolution of reversed forks rather than its cleavage that should require end-processing.